Apoferritin fibers: a new template for 1D fluorescent hybrid nanostructures. Issue 18 (22nd April 2016) - Jurado, Rocío; Castello, Fabio; Bondia, Patricia; Casado, Santiago; Flors, Cristina; Cuesta, Rafael; Domínguez-Vera, José M.; Orte, Angel; Gálvez, Natividad
Abstract : Apoferritin protein self-assembles to form amyloid-like fibers after heating, leaving numerous surface groups ready for functionalization with diverse fluorescent nanoparticles and dyes to obtain hybrid fluorescent materials. Abstract : Recently, research in the field of protein amyloid fibers has gained great attention due to the use of these materials as nanoscale templates for the construction of functional hybrid materials. The formation of apoferritin amyloid-like protein fibers is demonstrated herein for the first time. The morphology, size and stiffness of these one-dimensional structures are comparable to the fibers formed by β-lactoglobulin, a protein frequently used as a model in the study of amyloid-like fibrillar proteins. Nanometer-sized globular apoferritin is capable of self-assembling to form 1D micrometer-sized structures after being subjected to a heating process. Depending on the experimental conditions, fibers with different morphologies and sizes are obtained. The wire-like protein structure is rich in functional groups and allows chemical functionalization with diverse quantum dots (QD), as well as with different Alexa Fluor (AF) dyes, leading to hybrid fluorescent fibers with variable emission wavelengths, from green to near infrared, depending on the QD and AFs coupled. For fibers containing the pair AF488 and AF647, efficient fluorescence energy transfer from the covalently coupled donor (AF488) to acceptor tags (AF647) takes place. Apoferritin fibers are proposed here as a new promising template for obtaining hybrid functional materials.